ANALISA PENGARUH VARIASI KECEPATAN PUTARAN DAN FEED RATE PROSES PEMBUBUTAN TERHADAP KEKASARAN PERMUKAAN DAN LAJU KOROSI BAJA KARBON SEDANG - Ramadhan, Fahri; Matheus, J; Nanulaita, Nevada. JM; Malakauseya, J. J (Journal Mechanical Engineering, 2024)
a machine tool used to remove part of a rotated object is called a lathe. In the turning process, surface roughness often occurs on the workpiece, this roughness will later have an impact on the corrosion rate. In the oil and gas industry, corrosion is something that is very undesirable, because it can cause losses and also slow down a production process. This study aims to obtain the value of surface roughness and corrosion rate on medium carbon steel through the turning process with variations in rotation speed, namely at Rpm 350 and Rpm 460 with Vf 17 mm/minute, 21 mm/minute, 23 mm/minute, and 28 mm/minute. The results of this study are that the rotation speed and feed rate affect the roughness value on the surface of medium carbon steel, the average for Rpm 350 with Vf 17 the Ra value is 6.57 µm and Rz 31.2 µm, for Rpm 350 with Vf 21 the Ra value is 10.12 µm, and Rz 42.8 µm, for Rpm 460 with Vf 23 the Ra value is 6.53 µm and Rz 26.2 µm, and for Rpm 460 with Vf 28 the Ra value is 7.65 µm and Rz 34.4 µm. High Rpm but low Vf can produce lower surface roughness compared to low Rpm but high Vf. The surface roughness of the object also affects the corrosion rate, the specimen with the highest surface roughness, namely Rpm 350 with Vf 21, gets the highest corrosion rate value, namely 0.01086 mm/year. for the lowest surface roughness, namely Rpm 460 with Vf 23, gets a value of 0.00890 mm/years. it is proven that the higher the surface roughness value, the higher the corrosion rate value. Keywords: lathe, medium carbon steel, surface roughness, corrosion rate